1998
DOI: 10.1089/jwh.1998.7.575
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Autonomic Function Induced by Posture Change in Postmenopausal Women

Abstract: This study was designed to determine if there is a difference in autonomic regulation induced by posture change between postmenopausal and young women. To evaluate autonomic nervous system function, spectral analysis of heart rate variability (HRV) was done in postmenopausal women (n = 13, 46-59 years of age), age-matched men (n = 8, 45-55 years of age), and young women (n = 10, 20-37 years of age) for 3-min periods of controlled frequency breathing (15 breaths/min) in supine followed by sitting positions. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…One report about the features of the ANS function of climacteric women states that parasympathetic nerve activity decreases even during the regular menstrual cycle and the parasympathetic nerve reflex function also decreases when the woman changes body position 22 . In addition, ANS reflex function decreases in both parasympathetic and sympathetic nerves when the menstrual cycles of perimenopausal climacteric women are irregular 23 . The ANS activity tends to gradually decrease with age and the rate of the decline in parasympathetic nerve activity (HF) increases after the age of 40 years 24 .…”
Section: Discussionmentioning
confidence: 99%
“…One report about the features of the ANS function of climacteric women states that parasympathetic nerve activity decreases even during the regular menstrual cycle and the parasympathetic nerve reflex function also decreases when the woman changes body position 22 . In addition, ANS reflex function decreases in both parasympathetic and sympathetic nerves when the menstrual cycles of perimenopausal climacteric women are irregular 23 . The ANS activity tends to gradually decrease with age and the rate of the decline in parasympathetic nerve activity (HF) increases after the age of 40 years 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested that cardiac parasympathetic tone may be reduced in older persons in comparison with young women. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested that cardiac parasympathetic tone may be reduced in older persons in comparison with young women. [14] In the Framingham Heart Study, [15] plasma TGL is an independent predictor of coronary artery disease. This study presented with TGL level >140 mg/dl in postmenopausal age group in 35% of cases.…”
mentioning
confidence: 99%